PENGARUH FAKTOR-FAKTOR MEMOTIVASI KONSUMEN BERBELANJA TERHADAP KEPUTUSAN KONSUMEN BERBELANJA DI PASAR MODERN KOTA JAMBI - Mulyadi Raf (DIGEST MARKETING, 2012)
Modern markets which consist of many forms such as super market, department store, and malls, have recently grown rapidly in Jambi. Therefore, customers have many alternatives market where they can buy things they need. The purposes of this research is to examine how customer’s motivation factors which involve such variables as products, prices, services, and location, influenced the customers’ decision to buy things they need in modern market. Specifically, this research intended to study: a) were there any influence of products, prices, services, and location of modern market on customers’ decision to buy products at modern market; b) To what extent of these motivation variables influenced the customers’ decision to buy products at modern market; c) which variables influence most the decision of customers to buy products at modern market. Survey method using questioners was used to collect the data from respondents. Respondents were students at the Faculty of Economy of the University of Jambi, where 114 students were selected as the research samples. The samples were taken from the population of students using convenience sampling method. Multiple regression method was used as the main technique to analysis the data. The results of this research indicated that customers’ motivation factors consisting products, prices, services, and location of modern market significantly influenced the decision of customers to shop at modern market in term of both simultaneous and partial point of view. Products, which involved their quality, availability, and variety, influenced most among the variables used in the study.